A Human Leukemia Cell with Both B and T Cell Surface Receptors - Shevach, E. (1974)
Bone-marrow-derived (B) and thymus-derived (T) lymphocytes can be distinguished by the presence of a number of receptors and differentiation antigens. The presence of these markers has facilitated the identification and characterization of the mononuclear cells in a number of animal and human lymphoid malignancies. We describe here the immunological properties of human leukemia cells that are highly unusual, since they simultaneously bear the receptor for sheep erythrocytes characteristic of human T lymphocytes and the receptor for antigen-antibody-complement complexes characteristic of human B lymphocytes. A small number (about 2%) of normal human lymphocytes bearing both of these receptors was also identified.